PENGARUH DISTANSI TERHADAP TINGKAT KEBISINGAN YANG BERSUMBER DARI BUNYI MESIN KENDARAAN (STUDI KASUS PADA JALAN SUPRAPTO KOTA BENGKULU) - bahri, samsul; Saputra, Ari; Razali, Makmun Reza (Universitas Bengkulu, 2019)
Noise on a road is caused by the sound of a vehicle engine which is passing on. It can make the environment uncomfortable and the health problems in humans. The distance between the object and the sound source determines the magnitude of this impact. This study aims to look for the effect of the distance on noise levels that caused by vehicle engine sounds. The study was conducted in the central of Bengkulu City, Jalan Suprapto. Observations were made in 2 segments of Suprapto Road with 10 m distance intervals perpendicular to the sound source with a total of 5 points. The mathematical model uses the linear regression equation approach. Distance is an independent variable and noise is an independent variable. The results showed that, the relationship between the distance of the observation point and the noise value obtained equation Y = -0,317x+71,20 with R2 = 0,984.Keywords: noise, distortion, regression.